Drug delivery via super-paramagnetic (N2)n[SiO2(OH)2]8 Core-Shell catalyst - Khosravi, Somayeh; Monajjemi, Majid (Revista de la Universidad del Zulia, 2020)
The MNPs @ [SiO2(OH)2]8 catalyzers were stablished via ab-initio and quantum mechanics & Molecular mechanic (QM/MM) simulation. The studies focus on how to improve the dispersion of composite particle for achieving high magnetic performances. The results revealed that the Fe3O4 @[SiO2 (OH)2]8(N2)8 as a cabalist exhibited better thermodynamic stability and dispersion than the magnetite nanoparticles. Furthermore, the particle size and magnetic properties of the [SiO2 (OH)2]8(N2)8 composite nanoparticles can be controlled by changing the functional groups. The electrical properties such as NMR Shielding, electron densities, energy densities, potential energy densities, ELF, LOL, of electron density, eta index, ECP, ESR and hyperfine interactions for Fe3O4@ [SiO2(OH)2]8(N2)8 have been calculated. As the catalyst could be easily recovered by magnetic separation and recycled for a few times without significant loss of its catalytic activity, we have calculated to obtain the stronger non bonded interaction in the Fe3O4@ [SiO2(OH)2]8(N2)8 system. This system can be used for antibiotics drug delivery instead of injection. The chemical shielding and several factors as the same electronegativity, magnetic anisotropy of π-systems will be changed due to the number of electrons The chemical shielding is a vector orientation function for all of the shielding parameters that can change in several places inside the shielding region.